Molecular analysis of three Clostridium difficile strain genomes isolated from pig farm-related samples. (December 2017) - Martín-Burriel, I.; Andrés-Lasheras, S.; Harders, F.; Mainar-Jaime, R.C.; Ranera, B.; Zaragoza, P.; Falceto, V.; Bolea, Y.; Kuijper, E.; Bolea, R.; Bossers, A.; Chirino-Trejo, M.
Abstract: Clostridium difficile is an anaerobic spore-forming bacillus that usually causes gastrointestinal disorders in man and other animal species. Most of the strains isolated from animals are toxigenic being the virulent ribotype (RT) 078 predominant in several animal species. Although C. difficile is pathogenic to both humans and animals, there is no direct evidence of zoonosis. Deep genome sequencing provides sufficient resolution to analyse which strains found in animals might be related to human pathogens. So far, there are only a few fully sequenced genomes of C. difficile strains isolated from domestic and wild animals. Using Illumina technology, we have sequenced the genome of three isolates; a strain isolated from the vagina of a sow (5754), one from rat ( Rattus spp) intestinal content (RC10) and a third one isolated from environmental rat faeces (RF17). Both, rat and rat faeces were sampled in fattening pig farms. Our study reveals a close genetic relationship of two of these isolates with the virulent strain M120 (RT078) isolated from a human patient. The analysis of the sequences has revealed the presence of antibiotic resistance genes, mobile elements, including the transposon linked with virulence Tn 6164, and the similarity of virulence factors between these isolates and human strains. This is the first study focused on the sequencing of C. difficile genomes obtained from wild animals like rats, which can be considered as potential reservoirs for humans and other animal species. This study can help to understand the genome composition and epidemiology of this bacterium species. Highlights: Three pig farm-related Clostridium difficile strains were genome sequenced. Pig and environmental strains displayed high similarity with human M120 isolate. All of them displayed similarity with human Clostridium difficile isolates. Genomes harboured antibiotic-resistance, transposon and bacteriophage related genes.